2019
DOI: 10.1002/elan.201800638
|View full text |Cite
|
Sign up to set email alerts
|

Study on Combined Optical and Electrochemical Analysis Using Indium‐tin‐oxide‐coated Optical Fiber Sensor

Abstract: In this work an optical fiber sensor, where a lossy‐mode resonance (LMR) effect was obtained due to indium tin oxide (ITO) thin overlay, has been simultaneously applied as a working electrode in a 3‐electrode cyclic voltammetry electrochemical setup. Since LMR conditions highly depend on refractive index of a surrounding medium, an LMR‐based sensor was applied for optical investigations of electrolyte's properties at the ITO surface. We have found that the optical response of the sensor highly depends on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 37 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…In general, current follows E , and the changes in current show capacitive character. Capacitive current originates from the alternate charging and discharging of the electrical double layer formed at the electrode–electrolyte interface . The magnitude of this current is mainly related to the area of the sensor’s surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, current follows E , and the changes in current show capacitive character. Capacitive current originates from the alternate charging and discharging of the electrical double layer formed at the electrode–electrolyte interface . The magnitude of this current is mainly related to the area of the sensor’s surface.…”
Section: Resultsmentioning
confidence: 99%
“…Capacitive current originates from the alternate charging and discharging of the electrical double layer formed at the electrode−electrolyte interface. 52 The magnitude of this current is mainly related to the area of the sensor's surface. However, reducing the ITO-coated area would also affect the LMR, mainly its absorption depth profile.…”
Section: Experimental Studies On the Dielectric Layer Impact On The E...mentioning
confidence: 99%
“…We concluded that the ITO could lead to the enhancement of the electrochemical signals and the optical signals based on the LMR phenomenon. In the past, it has already been demonstrated that dual-domain sensing capability in electrochemical and optical domains can be offered by LMR sensors based on ITO film [ 50 ]. Moreover, ITO is assumed to be selective for the detection of the antibiotic ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we determine the refractive index and electroactive species with the LMR fiber sensor under an applied potential. LMR sensors with an ITO electrode were reported by Śmietana et al, [30][31][32] who investigated the sensor's optical response, effect of electrolyte, and applicability to biosensing (specifically, to avidin-biotin interaction). Our present study introduces two types of novel LMR sensing techniques for determining refractive indices of materials during the potential application.…”
Section: Introductionmentioning
confidence: 99%